2021
DOI: 10.1021/acsomega.1c00340
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modeling of Salting Effects in Solvent Extraction of Cobalt(II) from Chloride Media by the Basic Extractant Methyltrioctylammonium Chloride

Abstract: The design and optimization of solvent extraction processes for metal separations are challenging tasks due to the large number of adjustable parameters. A quantitative predictive solvent extraction model could help to determine the optimal parameters for solvent extraction flow sheets, but such predictive models are not available yet. The main difficulties for such models are the large deviations from ideal thermodynamic behavior in both the aqueous and organic phases due to high solute concentrations. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Extractants consisting of a quaternary ammonium cation with long alkyl chains and a counteranion typically organize into reverse micellar structures due to their surfactant-like properties. Most of the water in the organic phase is then found inside these reverse micelles. This can also explain the large amount of water that can be dissolved in organic phases with a high quaternary ammonium extractant concentration . It is now possible to come back to the unexpected trend in the distribution of acids to the organic phase (Figure ).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Extractants consisting of a quaternary ammonium cation with long alkyl chains and a counteranion typically organize into reverse micellar structures due to their surfactant-like properties. Most of the water in the organic phase is then found inside these reverse micelles. This can also explain the large amount of water that can be dissolved in organic phases with a high quaternary ammonium extractant concentration . It is now possible to come back to the unexpected trend in the distribution of acids to the organic phase (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…This can also explain the large amount of water that can be dissolved in organic phases with a high quaternary ammonium extractant concentration. 39 It is now possible to come back to the unexpected trend in the distribution of acids to the organic phase (Figure 3). It was observed that the more hydrophilic HCl is distributed more to the organic phase than the more hydrophobic HBr.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…136 Nevertheless, the road is long, and better theories need to be developed for every aspect of colloidal soft-matter approaches, especially if they are to be applied to the nonequilibrium transfer of ions, where the hysteresis of backextraction cannot be obtained. Also, improvements in the modeling in the aqueous phase 137 to decipher phenomena such as the co-ion specificity (e.g., NO 3 − vs Cl − ) or the boost in extraction efficiency when using the background, nonextracted salt 22 are very important. The challenge remains to obtain the activities and speciation of all solutes in supersaturated solutions, with the aim of better modeling of the polar core of the aggregate.…”
Section: ■ Conclusionmentioning
confidence: 99%